Self-Regulated Learning and a Sense of Achievement in MOOCs Among High School Science and Technology Students. Issue 2 (2nd April 2016) - Cohen, Lizi; Magen-Nagar, Noga
ABSTRACT: This study, conducted in Israel, examined how learning strategies and motivational orientations contributed to high school students' sense of achievement in a massive open online course. The objective was to integrate an innovative teaching–learning strategy into the educational system that is based on online learning for students in subjects that are rich in knowledge and technology. The researchers used a motivated strategies learning questionnaire modified to fit the purpose of this study. In addition, the researchers built and used a sense of achievement index based on social pedagogy as a leading principle in the current learning model. Structural Equation Modeling path analysis results suggested that projects-based learning subjects had a significant positive impact on motivational orientations and learning strategies, and they in turn had a significant positive impact on students' sense of achievement.